Kryminał edukacyjny dla młodzieży na przykładzie serii "Pan samochodzik" Zbigniewa Nienackiego = Zbigniew Nienacki's "Pan samochodzik" ("Mr. Car") series as an example of educational crime novel for teenagers - Peroń, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Zbigniew Nienacki's "Mr. Car" series consists of twelve volumes which appeared between 1964 and 1985. The books, destined for the young readers, combine two genres - crime and educational novel. The former uses a pattern of a detective searching for stolen culture items, while the latter involves issues connected with the history and geography of Poland. In order to make the ideological message attractive, the author combines it with adventure. The educational aspect of the novel is reflected in the construction of the characters. The protagonist is an adult authority figure for the young characters.
Keywords: literatura dla dzieci i młodzieży; Nienacki, Zbigniew (właśc. Nowicki, Zbigniew Tomasz; 1929-1994); powieść kryminalna